6-(2y-6)=9-3y

Simple and best practice solution for 6-(2y-6)=9-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(2y-6)=9-3y equation:


Simplifying
6 + -1(2y + -6) = 9 + -3y

Reorder the terms:
6 + -1(-6 + 2y) = 9 + -3y
6 + (-6 * -1 + 2y * -1) = 9 + -3y
6 + (6 + -2y) = 9 + -3y

Combine like terms: 6 + 6 = 12
12 + -2y = 9 + -3y

Solving
12 + -2y = 9 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
12 + -2y + 3y = 9 + -3y + 3y

Combine like terms: -2y + 3y = 1y
12 + 1y = 9 + -3y + 3y

Combine like terms: -3y + 3y = 0
12 + 1y = 9 + 0
12 + 1y = 9

Add '-12' to each side of the equation.
12 + -12 + 1y = 9 + -12

Combine like terms: 12 + -12 = 0
0 + 1y = 9 + -12
1y = 9 + -12

Combine like terms: 9 + -12 = -3
1y = -3

Divide each side by '1'.
y = -3

Simplifying
y = -3

See similar equations:

| (1+g)sqrt(k)+4k=1 | | 4=3x+5(x+4) | | a-10b/8a-5a-11b/8a | | 5+6r-3=7r+8-3r | | 3(y-7)-8y=4 | | 7y+4=8y | | 0.02/0.7 | | 7(x-9)+6(4x-7)=30(x-4)-3 | | g=3h+5 | | g=4h+1 | | 5.6(4+4x)-9.4=13 | | 4(u+2)-7u=17 | | 0.7/0.02 | | 5/6-(1/18) | | 5.3=x(x+.6)(x-.1) | | 5/8-(1/8) | | 1/5x-3/8y=12 | | 4y+1-2y=3+y+9 | | -4w-2/3=7/5w-4/5 | | -8(n+8)=2-7n | | -10a+40=9 | | X(t)=1-u(t-3)+(t*u(t-3)) | | 8/9x=8+4/9 | | 12a^3/5a | | 6t^2-36t+48= | | 55-8x= | | (X-5)+X=82 | | 3u-25=2u | | 5w+7-2=5+4 | | (X+5)+x=82 | | 12x-22/132 | | 5r^2+6r-1=0 |

Equations solver categories